In the Making of Mobility Regimes in Africa - (:unkn) unknown (My University, 2024)
In Africa, debates about the making of migration policies and mobility regimes are at the heart of many studies. For the past twenty years, discussions around the transformation of mobility regimes, the strengthening of borders and the emergence of multiple migration “management” actors have mainly been addressed through the lens of border externalization processes and the role of international migration governance actors. This thematic folder seeks to offer a different and fresh perspective by focusing on the historical, social and political trajectories specific to African states and their societies in the governance of mobilities. It examines how a wide range of actors, both state and non-state, engage with, contest and or repurpose the socio-political spaces of migration governance through their practices, discourses, or mobilities. This thematic folder thus aims to shed light on the existence of political, social and economic dynamics specific to African states, which, according to their own agendas, capitalize on the diverse opportunities offered by external actors and cooperation in the fields of migration, security, development aid and democracy. Finally, by moving beyond a strictly technical reading of migration policies, this thematic folder highlights the deep fractures between states and their citizens: the criminalization of mobility and the repressive practices targeting migrants.
Keywords: African Research